PESAN DAKWAH DI DALAM SURAH AL LAIL - Tabsyir Masykar (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
Message in the communication process is something conveyed by communicators to the communicant. Which is the message, ideas, ideas, information, and opinions that are conveyed by a sender of the message (communicator) to the recipient of the message (communicant) whose purpose is to influence it to follow the attitude that is conveyed to him. Where as Da'wah is an invitation to the right path that is Islam which is blessed by Allah. Therefore it is necessary to have an important message of da'wah that must be conveyed in the communication process. Where the main source of Islamic teachings is the first is the Qur'an and one of them is surah al lail. Surah al lail is a makkiah surah consisting of 21 verses which has very important material in preaching such as da'wah messages including the content of the verses relating to aqeedah, syari'ah and akhlak, so that this is clearly what the message of the surah wants to convey